THE DISCURSIVE IDENTITY OF THE JAKARTA POST ON THE FUEL ISSUE OF INDONESIA 2012 IN THE SELECTED EDITORIALS - Yurinda, Meike Tri (2013)
The research paper is entitled The Discursive Identity of The Jakarta Post on the Fuel Issue of Indonesia 2012 in the Selected Editorials. It is aimed at investigating how the discursive identity of The Jakarta Post on the fuel issue of the first semester of Indonesian government 2012 is constructed in the selected editorials and discovering its ideological message on that issue. Two data sources of editorials, Editorial : Huffing and puffing over fuel and Editorial : Only an ad-hoc fuel measure, were taken from on-line version of The Jakarta Post related to the chosen issue. The Fairclough's approach to Critical Discourse Analysis (1995) was employed as the basic framework to analyze the tools of modality and evaluation (Halliday, 1994; Martin, 1995; Martin, Matthiessen, & Painter, 1997; Fairclough, 2003; Halliday & Matthiessen, 2004; Eggins, 2004) in the area of Systemic Functional Grammar (Halliday, 1994) in examining the identity of The Jakarta Post on the chosen issue discursively. The results of the study show that The Jakarta Post tends to construct its identity on the fuel issue by showing several commitments, namely its commitment to several good possibilities if the option of raising subsidized fuel price is chosen; to the policy of maintaining fuel subsidies labeled negative things and impacts on Indonesia's government and condition; and to the importance of the role of relevant parties. By those three commitments, The Jakarta Post seems to deliver the message of opposing fuel subsidies to its readers